Assistance Practice of Welcoming Speech for Students of Veteran I Senior High School: Pendampingan Praktik Welcoming Speech Bagi Siswa SMA Veteran I - Tri Widarwati, Nunun; Astuti, Purwani Indri; Wijayava, Ratih (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The service activity aims to strengthen Public Speaking, especially the Welcoming Speech for Veteran I High School Students in Sukoharjo. The activity method is offline face to face with lecture and practice methods. The training participants were Veteran I High School students in Sukoharjo. Activity Location at Veteran I Sukoharjo High School. The results achieved were that offline face-to-face service activities resulted in an increase in pre-test and post-test scores of 48 percent, the highest score was 90, the lowest score was 75 and the average score was 87. Apart from that, the results of the activity were also in the form of YouTube videos for each participant of Welcoming Speech. The result of the Practice Video score was that the average score was 82.4 points with a good letter conversion. The highest score was obtained with 88 points with excellent value. There were 50 percent of students who got an A grade. Based on these results, it shows that the students participating in Community Service were able to practice welcoming speech with good grades. Students are able to absorb the transfer of knowledge from service speakers. The benefits of the activity are increasing fluency in Public Speaking in the Welcoming Speech and improving Public Speaking practice for Veteran I High School Students in Sukoharjo.